2011
DOI: 10.3109/01676830.2011.584931
|View full text |Cite
|
Sign up to set email alerts
|

Facial Asymmetry and Nasal Septal Deviation in Acquired Nasolacrimal Duct Obstruction

Abstract: Unilateral nasolacrimal duct obstruction appears to occur on the side in which the nasal septum is deviated. There is a trend of nasal septal deviation toward the smaller side of the face. Further prospective studies are needed to clarify the above relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
2
11
0
2
Order By: Relevance
“…Many investigators have tried to determine whether there is a relationship between nasal septal deviation and facial asymmetry, and they demonstrated that there is a positive relationship between nasal septal deviation (NSD) and facial growth. [4][5][6]10,11 However, previous studies on the role of nasal septum in facial asymmetry have certain limitations, and controversy still exists over these studies. Previous studies have some limitations with respect to the evaluation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Many investigators have tried to determine whether there is a relationship between nasal septal deviation and facial asymmetry, and they demonstrated that there is a positive relationship between nasal septal deviation (NSD) and facial growth. [4][5][6]10,11 However, previous studies on the role of nasal septum in facial asymmetry have certain limitations, and controversy still exists over these studies. Previous studies have some limitations with respect to the evaluation.…”
mentioning
confidence: 98%
“…6 Taban emphasized that there is a trend for nasal septal convexity toward the smaller side of the face. 5 Kim suggested that facial asymmetry patients have a wider midfacial width in the direction of nasal septal convexity. In this study, we aimed to evaluate the integrated relationship between nasal septal deviation and facial asymmetry by means of 3-dimensional analysis in a larger number of patients than those in previous studies.…”
mentioning
confidence: 99%
“…Turbinate hypertrophy involves an increase in the size of the mucosa, which may cause drainage disorders that affect ciliary function, leading to secondary obstruction and infection (Gencer et al, 2013). In fact, nasolacrimal duct obstruction are observed on the concave side of the nasal septum (Taban et al, 2011). Lee et al (2013) reported that the higher degree of facial asymmetry and nasal septal deviation was associated with increased nasolacrimal duct obstruction (Lee et al).…”
Section: Discussionmentioning
confidence: 99%
“…There are claims that unilateral NLD duct obstruction is related to septal deviation and tends to happen at the smaller side of face (Taban et al, 2011). Functional nasolacrimal obstruction is less common.…”
Section: Nasolacrimal Duct and Endoscopic Dcrmentioning
confidence: 98%